Ontogeny of NO synthase and renin in juxtaglomerular apparatus of rat kidneys - Fischer, Evelyne; Schnermann, Jürgen; Briggs, Josie P.; Kriz, Wilhelm; Ronco, Pierre M.; Bachmann, Sebastian (American journal of physiology, 1995)
The presence of NO synthase (NOS) in cells of the macula densa (MD) suggests a role for arginine-derived NO in tubulovascular information transfer. To investigate the postnatal development of the neuronal isoform of NOS and of renin in the kidney, the cellular distribution of these enzymes was examined in perfusion-fixed kidneys of 2-, 6-, and 15-day-old rats at both the protein and mRNA level (n = 4 rats/group). NOS and renin and their mRNAs were localized by immunohistochemical and in situ hybridization methods. In addition, NOS levels were assessed by using NADPH diaphorase (NADPH-d) histochemistry. For quantification, the fraction of NOS- and renin-positive glomeruli as well as the number of NOS-positive MD cells was evaluated at all stages. Presence of NOS in single cells of the developing distal tubule was encountered already in the S-shaped body. Full expression of a NOS signal in MD cells was seen as soon as a glomerular urinary space was developed. Double labeling with NADPH-d and antibody to Tamm-Horsfall protein (THP) indicated mutual exclusiveness of NADPH-d-positive MD cells and neighboring THP-positive distal tubule cells at all levels of development. The relative intensity of renin status was 2 day > 6 day > 15 day, whereas NOS expression was maximal on postnatal day 6. Our data are consistent with an involvement of MD NO synthesis in the early organization of the juxtaglomerular apparatus during nephrogenesis and suggest an interdependent relation with renin-producing cells.
Gesehen am 23.11.2023